Seasonal Dynamics in Dissolved Organic Matter, Hydrogen Peroxide, and Cyanobacterial Blooms in Lake Erie - Cory, Rose M.; Davis, Timothy W.; Dick, Gregory J.; Johengen, Thomas; Denef, Vincent J.; Berry, Michelle A.; Page, Sarah E.; Watson, Susan B.; Yuhas, Kate; Kling, George W. (Frontiers in Marine Science, 2016)
Hydrogen peroxide (H2O2) has been suggested to influence cyanobacterial community structure and toxicity. However, no study has investigated H2O2 concentrations in freshwaters relative to cyanobacterial blooms when sources and sinks of H2O2 may be highly variable. For example, photochemical production of H2O2 from chromophoric dissolved organic matter (CDOM) may vary over the course of the bloom with changing CDOM and UV light in the water column, while microbial sources and sinks of H2O2 may change with community biomass and composition. To assess relationships between H2O2 and harmful algal blooms dominated by toxic cyanobacteria in the western basin of Lake Erie, we measured H2O2 weekly at six stations from June to November, 2014 and 2015, with supporting physical, chemical, and biological water quality data. Nine additional stations across the western, eastern, and central basins of Lake Erie were sampled during August and October, 2015. CDOM sources were quantified from the fluorescence fraction of CDOM using parallel factor analysis (PARAFAC). CDOM concentration and source were significantly correlated with specific conductivity, demonstrating that discharge of terrestrially-derived CDOM from rivers can be tracked in the lake. Autochthonous sources of CDOM in the lake increased over the course of the blooms. Concentrations of H2O2 in Lake Erie ranged from 47 ± 16 nM to 1570 ± 16 nM (average of 371 ± 17 nM; n = 225), and were not correlated to CDOM concentration or source, UV light, or estimates of photochemical production of H2O2 by CDOM. Temporal patterns in H2O2 were more closely aligned with bloom dynamics in the lake. In 2014 and 2015, maximum concentrations of H2O2 were observed prior to peak water column respiration and chlorophyll a, coinciding with the onset of the widespread Microcystis blooms in late July. The spatial and temporal patterns in H2O2 concentrations suggested that production and decay of H2O2 from aquatic microorganisms can be greater than photochemical production of H2O2 from CDOM and abiotic decay pathways. Our study measured H2O2 concentrations in the range where physiological impacts on cyanobacteria have been reported, suggesting that H2O2 could influence the structure and function of cyanobacterial communities in Lake Erie.